2015
DOI: 10.1111/1754-9485.12393
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic reaction dose for parenchymal changes on Gd‐EOBDTPA‐enhanced magnetic resonance images after stereotactic body radiation therapy for hepatocellular carcinoma

Abstract: The threshold dose for parenchymal changes in the hepatobiliary phase of Gd-EOB-DTPA-enhanced MR images performed 2-4 months after 45 Gy of SBRT in three fractions was approximately 20 Gy. Our results provide the basis for further research on the functional loss of liver parenchyma after SBRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Therefore, the early detection and diagnosis of acute RILD are of great significance for the restorative treatment of the liver. At present, the common examination methods for RILD are CT and MRI, but there is no specific imaging manifestation of early-stage RILD on CT and MRI (3,4). CEUS displays the microcirculation of tissues and organs and the imaging effect is consistent with that of enhanced CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the early detection and diagnosis of acute RILD are of great significance for the restorative treatment of the liver. At present, the common examination methods for RILD are CT and MRI, but there is no specific imaging manifestation of early-stage RILD on CT and MRI (3,4). CEUS displays the microcirculation of tissues and organs and the imaging effect is consistent with that of enhanced CT and MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored effective ways to diagnose and treat early-stage RILD, including the establishment of animal models of RILD and investigation of/using certain imaging methods. However, previous imaging studies using modalities including CT, MRI or single-photon emission CT, focused mainly on the discovery of morphological changes associated with RILD and were limited by the duration of the disease, and accordingly, their clinical application is currently limited (3,4). Previous experimental studies on RILD in animals have demonstrated that contrast-enhanced ultrasound (CEUS) is able to directly reflect changes in the circulating dynamics of microvessels in early-stage RILD (5).…”
Section: Introductionmentioning
confidence: 99%
“…The Quantitative Analysis of Normal Tissue Effect in the Clinic (QUANTEC) recommends a mean normal liver dose (excluding the GTV) < 15 Gy for 3 fractions, and < 20 Gy for 6 fractions in HCC patients receiving SBRT, and at least 700 cc of normal liver volume receiving < 15 Gy in 3 or 5 fractions [14]. In our recent study investigating the threshold dose for hepatic parenchymal changes on gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced MRI images after SBRT for HCC [25], the hepatic parenchymal reaction dose for the parenchymal changes in the hepatobiliary phase of the enhanced MRI images performed 2–4 months after 45 Gy was delivered in 3 fractions, was approximately 20 Gy. Nevertheless, given that the understanding of the normal liver dose constraints was generally derived from retrospective chart reviews or via mathematical modeling, all dose recommendations are associated with some uncertainty and should be interpreted cautiously.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed procedure for liver SBRT at our institution has been described in previous reports [25, 26]. If appropriate surrogates for tumor localization, including surgical clips or compact iodized oil remaining from previous treatments were available, they were used for tumor localization during treatment (n = 20).…”
Section: Methodsmentioning
confidence: 99%
“…Lack of washout on delayed phase in hypervascular areas helps distinguish SBRT-related change from residual/recurrent HCC [41]. Focal liver reaction to SBRT (not to be misread as recurrent HCC) has a threshold dose of 30 Gy/5 fractions for Child-Pugh A and 25 Gy/5 fractions for Child-Pugh B [42,43] or 20 Gy/3 fractions [44]. Of note, uncertainty exists between the imaging changes, the pathological fibrosis, and the serological data.…”
Section: Post-sbrt Imagesmentioning
confidence: 99%